Agroexports, economic growth and labor rights - Gamero Requena, Julio (2011)
The boom in agricultural exports is undeniable. These have doubled in the last ten years and their destination markets have diversified along with the expansion of the product portfolio. The number of salaried workers in this activity amounts to more than 200 thousand, however, their salary and employment conditions are far from decent work standards and do not correspond to the remarkable expansion of this sector. Why is this situation? This article develops the hypothesis that this is due to the persistence of an inequitable labor arrangement that was established at the beginning of the 1990s. In the 1990s, the so-called “boom” of agro-exports began. Traditional agricultural exports -coffee, cotton, corn- began to be displaced by growing flows of other products that were called non-traditional, including asparagus, vegetables, fruits and cereals.